The Relationship between Parenting Styles and Adolescents’ Social Anxiety in Migrant Families: A Study in Guangdong, China - Xu, Jihong; Ni, Shiguang; Ran, Maosheng; Zhang, Chengping (Frontiers in Psychology, 2017)
Previous studies indicated that parenting styles were important influencing factors for the development of children’s well-being. It is known that mass migration to the cities in China will affect family relations. However, few studies focused on the relationship between parenting styles and adolescents’ mental health in migrant families. Thus, this study aimed to investigate how parenting styles could affect adolescent’s social anxiety in migrant families. A total number of 1,345 adolescents in migrant families from four non-government-funded junior middle schools in Guangdong province formed the research sample. Parenting styles were measured using short-form of the Egna Minnen Beträffande Uppfostran, and social anxiety was evaluated using Social Anxiety Subscale of Self-Consciousness Scale. The results showed that emotional warmth, overprotection and rejection were significantly more often perceived from mothers than from fathers. Significant group differences between high social anxiety group and low social anxiety group were found in both father’s rearing styles and mother’s rearing styles. Furthermore, in migrant families, paternal emotional warmth could decrease adolescents’ social anxiety, whereas maternal overprotection could increase it.